2023
DOI: 10.1111/ajps.12769
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism, Trust, and Identity: Evidence from a Natural Experiment in Nigeria

Abstract: We study the effects of terrorism on political trust and national versus ethnic identification. Making use of unexpected attacks by the extremist group Boko Haram in Nigeria, which occurred during the fieldwork of a public opinion survey in 2014, we show that even in a context of weak state institutions and frequent terrorist activities, terror attacks significantly increase political trust. We also find that the attacks significantly reduced the salience of respondents' national identity, instead increasing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In a study conducted in the wake of a terrorist attack perpetrated by the radical Islamist group Boko Haram, Harding and Nwokolo (2023) found that exposure to violence weakened Nigerians' sense of national identity and strengthened their feeling of ethnic belonging. Analyzing survey data for Nigeria, found that exposure to violent conflict made Nigerians reluctant to have people of a different ethnicity and religion as neighbors.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…In a study conducted in the wake of a terrorist attack perpetrated by the radical Islamist group Boko Haram, Harding and Nwokolo (2023) found that exposure to violence weakened Nigerians' sense of national identity and strengthened their feeling of ethnic belonging. Analyzing survey data for Nigeria, found that exposure to violent conflict made Nigerians reluctant to have people of a different ethnicity and religion as neighbors.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Since the day and person interviewed are fixed in advance and not affected by the war, our design resembles a natural experiment: the invasion is a random shock to respondents who were interviewed just after the start of the war, which we then compare to respondents that were interviewed before the invasion began. This research design has been used to estimate the causal effect of other types of shocks on attitudes in previous research (27,(33)(34)(35).…”
Section: Main Textmentioning
confidence: 99%
“…Non-compliance could be an issue if, for instance, some members of the treatment group are not exposed to a treatment because they are unaware of its occurrence (Harding and Nwokolo, 2023). While we cannot directly test for or rule out non-compliance, we think that it is unlikely to be a significant concern for three reasons.…”
Section: In Thementioning
confidence: 93%
“…The estimates may also be biased because of attrition and non-compliance (Gerber and Green, 2012;Harding and Nwokolo, 2023). We check for attrition bias (systematic drop-out by respondents) by estimating the correlation between treatment status and item non-response for our outcome variable.…”
Section: In Thementioning
confidence: 99%
See 1 more Smart Citation